2013
DOI: 10.3329/bjar.v37i4.14397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different packaging systems and chlorination on the quality and shelf life of green chili

Abstract: The experiment was conducted to evaluate the effect of packaging materials on the quality and shelf life of green chili (Capsicum annuum) using passive modification of modified atmosphere packaging system. The modified atmosphere was created by making perforation in the polypropylene packets. Green chili pre-treated with chlorine water and then packaging in 0.3% perforated polypropylene packet resulted substantial reduction of weight loss and rotting/shriveling. These treatment combinations also considerably r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…However, packing fresh garlic bulbs in polypropylene (PP) or polyethylene (PE) showed a significant lower decrease in weight loss % during storage, without any significant difference between them in the second and third seasons. Such result, are in agreement with those of Rahman et al (2012) on green chili pepper. On the other hand, the highest value of weight loss was observed in the control and followed by net packages.…”
Section: The Storage Experiments 321 Weight Loss Percentagesupporting
confidence: 93%
See 1 more Smart Citation
“…However, packing fresh garlic bulbs in polypropylene (PP) or polyethylene (PE) showed a significant lower decrease in weight loss % during storage, without any significant difference between them in the second and third seasons. Such result, are in agreement with those of Rahman et al (2012) on green chili pepper. On the other hand, the highest value of weight loss was observed in the control and followed by net packages.…”
Section: The Storage Experiments 321 Weight Loss Percentagesupporting
confidence: 93%
“…Application of plastic bag packaging maintains freshness and shelf life of Chinese kale (Niyomlao et al, 2000). Also, Rahman et al (2012) found that packing green chili pepper (Capsicum annuum) in polypropylene (PP) bags maintained moisture, reduced weight loss and prevented shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Kadar vitamin C cenderung semakin menurun sebanding dengan semakin lamanya waktu penyimpanan (Tabel 4). Hal ini sesuai dengan hasil penelitian Wulandari et al (2012), Rahman et al (2012), dan Chitravhanti (2015) yang menunjukkan bahwa semakin lama waktu penyimpanan maka kadar vitamin C pada buah akan semakin menurun. Vitamin C biasanya terdegradasi atau rusak karena proses oksidatif.…”
Section: Hasil Dan Pembahasanunclassified
“…Packaging is an activity to protect the freshness of agricultural products during transportation, distribution and storage. Packaging can slow down the respiration process so that it can extend the shelf life of vegetables and fruits [4]. The results of the research by [5] stated that the use of cardboard packaging can maintain the quality of chilies better than sack packaging at a temperature of 10 ° C for up to seventeen days of storage.…”
Section: Resultsmentioning
confidence: 99%